Коштовності з с. Коробчине на Дніпропетровщині - Приходнюк, О.М.; Чурилова, Л.М. (Археологія, 2001)
Публікація присвячена аналізу та науковій інтерпретації супровідного інвентаря з поховання мадярського вельможі з с. Коробчине Криничанського р-ну Дніпропетровської обл. В окрестностях с. Коробчино Криничанского р-на Днепропетровской обл. в 1989 г. при земляных работах были обнаружены вещи, сопровождавшие захоронение воина-кочевника с конем. На хранение в Днепропетровский исторический музей поступили следующие предметы: железные сабля, стремя и 2 стрелы; серебряные с позолотой 2 звена от обкладок ножен сабли, блюдо и чаша восточного происхождения, серебряный и золотой браслеты, 10 золотых круглых бляшек, фрагмент глиняного гончарного кувшина. Орнаментика верхнего звена оковки ножен (сеть с удлиненными трилистниками внутри ячеек) и круглых бляшек (сердцевидный орнамент) является свидетельством того, что в с. Коробчино был погребен знатный угр периода до переселения венгров в Подунавье (конец IX в.). In the vicinity of the village of Korobchyne, the Krynychansky district, the Dnipropetrovsk region, things accompanied by a soldier-nomad with a horse were found on excavations in 1989. The following things were delivered to the Dnipropetrovsk historical museum for storage: an iron saber, stirrup, and two arrows; two links of the facing of the saber’s sheath (silver with gilding); a dish and cup of the east origin; silver and gold bracelets; ten gold round plaques; and the fragment of a clay potter’s jug. The ornament of both the upper link of the sheath’s fitting (a network with elongated three-lobed figures inside cells) and round plaques (the hearth-like ornament) testifies that a noble Ugrian was buried at Korobchyne in the period before the migration of the Hungarians to the Danube region (the end of the IX century AD).